DISEMINASI TAUTAN DALAM GROUP FACEBOOK MAHASISWA JURUSAN JURNALISTIK FISIP UHO - Abdullah M Lamaaga (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2017)
The purpose of this study were (1). To know the type of facebook link journalism student FISIP U, (2). To know Link Dissemination in Facebook Group of Students Department of Journalism FISIP UHO, (3). To know the response of group members to the links in the Facebook Group of Students Department of Journalism FISIP UHO.The theory used in this research is the theory of Diffusion of Information / Innovation is that in 1962, Everret Rogers combines the findings of information flow research with studies on the flow of information and personal influences in several fields. From the theory described above this researcher examines the flow of information and personal in the dissemination of facebook links. The flow of information consists of two forms of simultaneous and consecutive forms.This research was conducted at Halu Oleo University Faculty of Social and Political Science majoring in journalism. Determination of informants done by purposive sampling as much as 7 people. The data collection technique is by way of observation, interviews, and documentation. The type of data used is qualitative data.The results of this study indicate that (1). Fisip UHO's facebook student facebook links vary widely including: Academic Information, Halu Oleo University, Advertising, Southeast Sulawesi Development, and Entertainment, (2) Dissemination link in Facebook Group of students majoring in journalism FISIP UHO includes a channel of information simultaneously that links shared by members in the group will be received simultaneously by all members and channels of sequential information this can happen when the admin tag (mark) one member account when going to share the link, at that point the first person to receive the information is the person tagged. Characteristics of the divider in the facebook group varies greatly and the divisor's motivation is not to trouble in finding information, especially about academic. (3) the responses of facebook group members to the group contents are various links that have been shared by each group member so it is very helpful for those who need the information and membership in the group facebook student journalism FISIP UHO it is assumed that the activity of the members is considered very helpful other members who want get information according to his needs.Keywords: Dissemination, Link, Group Facebook, Student Journalism Department